The role of sequential automation in improving process safety. Issue 2 (30th December 2014) - Huffman, David A.
<x xml:space="preserve">Abstract</x> Generally, process safety automation has been considered to be the responsibility of a specialized safety system and that remains true for Safety Integrity Level safety automation requirements. But, what if the basic automation of the process could be constructed in such a way that it significantly improved the ability to maintain the process within acceptable operating limits and not reach the conditions that would trigger a response from the safety system? All processes operate based on procedures, usually written. Batch‐based processes more and more run on automated procedures. But, even continuous processes constantly use procedures. Among these are equipment and unit startup and shutdown procedures, product or grade change procedures, spare equipment in and out of service procedures, quality control procedures, alarm response procedures, and many more. Frequently, there can be significant benefits to automating a high percentage of these procedures. Safety is one of those benefits and can be derived from opportunities ranging from consistent and mistake proof operations to simply removing the need for an operator to be exposed to potential process or physical hazards. Additionally, significant impacts can be realized on alarm management based on procedural control. © 2014 American Institute of Chemical Engineers Process Saf Prog 34: 199–201, 2015